Dinamika perkembangan ilmu pengetahuan: Zaman yunani kuno hingga abad pertengahan - Zahro, Eka Wardatuz (Maliki Interdisciplinary Journal, 2026)
The development of science is a long process influenced by social dynamics, culture, and human ways of thinking throughout history. Ancient Greece is recognized as the beginning of rational thought that replaced myths in explaining natural phenomena. Philosophers such as Socrates, Plato, and Aristotle played important roles in establishing the foundations of philosophy, logic, mathematics, astronomy, and natural sciences, which later became the basis of modern science. During the Middle Ages, the development of science in Europe declined due to the dominance of the Church and limited intellectual freedom, a period known as the Dark Ages. On the other hand, the Islamic world experienced the Golden Ages, marked by significant scientific progress through scholars such as Ibn Sina, Al-Khawarizmi, and Ibn Rushd. Islamic civilization played a major role in preserving, translating, and developing Greek knowledge, which later became a bridge toward the revival of science in Europe during the Renaissance. This study aims to explain the development of science from Ancient Greece to the Middle Ages and its influence on the emergence of modern scientific thought.